Pengaruh Model Pembelajaran Discovery Learning terhadap Kemampuan Berpikir Logis Siswa Kelas X MIA SMA Muhammadiyah 1 Surakarta Tahun Pelajaran 2013/ 2014 - Cahyani, Marina Rizki Tri; Dwiastuti, Sri; Maridi, Maridi (BIO-PEDAGOGI, 2014)
The purpose of the research was to determine effect of Discovery Learning on student’s logical thinking skills of grade X MIA SMA Muhammadiyah 1 Surakarta academic year 2013/2014. The study was a quasi experimental research with a Posttest Only Nonequivalent Control Group Design. The population was all students of class X MIA SMA Muhammadiyah 1 Surakarta in the school year 2013/2014. The sampling technique was cluster sampling. Data collection techniques using tests and non-test methods. Independent sample t-test was used to test hypothesis. The result of hypothesis testing has a significance of 0.048. The average value of logical thinking test on control class was 4.41 and the experimental class was 5.19. The conclusion was Discovery Learning significant effect on student’s logical thinking skills of grade X MIA SMA Muhammadiyah 1 Surakarta academic year 2013/2014. Key Words: Discovery Learning, logical thinking skills, conventional learning